The Contribution of Communication Climate and Achievement Motivation to the Performance of Elementary School Teachers - Rizki Rahayu; Amiruddin Siahaan; Makmur Syukri; Muhammad Husnur Rofiq (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The problem of this research can be formulated as follows: (1) does the communication climate contribute to the performance of teachers at the State Elementary School in Region 2 District of Kuala District? and (3) does the communication climate and achievement motivation jointly contribute to the performance of teachers in the State Elementary Schools of the Region 2 Cluster of Kuala Subdistrict This research method is a correlational quantitative research using descriptive and inferential approaches. In this study, the population was all teachers at the State Elementary School Cluster Region 2, Kuala District, amounting to 80 people. The sample of this study was taken by referring to the Krejcie-Morgan table where a fixed sample of 66 people was obtained. This research data collection using a questionnaire with a Likert scale. The results of data analysis show that: (1) communication climate contributes 32.2% to teacher performance; (2) achievement motivation contributes 12.3% to teacher performance; (3) The communication climate and achievement motivation together contribute 38.1% to the teacher's performance at the State Elementary School Cluster 2, Kuala District. Based on these findings, it can be concluded that communication climate and achievement motivation are two important factors that can contribute to teacher performance that cannot be ignored in addition to other variables not examined in this study.